Challenges of Instructional Leadership Related to Teacher Performance at Sabak Auh Junior High School - Lendra Sosana; Dwi Esti Andriani (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the challenges faced by the school principal in implementing instructional leadership to improve teacher performance at SMP Sabak Auh. Based on findings from the Education Report, although instructional leadership is categorized as good, the quality of teaching remains moderate. This indicates that despite the principal's active role in formulating a vision, managing learning programs, and creating a positive learning climate, the implementation has not fully impacted the quality of teaching. This research uses a qualitative approach with descriptive and phenomenological methods, collecting data through documentation, interviews, and observations. The findings show that the principal adopts a collaborative approach in setting learning goals, involving all teachers. However, the biggest challenge is the differing understanding among teachers regarding the implementation of these goals in the classroom, as well as the lack of technological skills among some teachers. The principal has implemented continuous training to address these challenges, but limited technological facilities and varying levels of teacher readiness remain obstacles. This study recommends strengthening the provision of technological facilities, enhancing training based on the practical needs of teachers, and increasing opportunities for teacher collaboration to improve teaching quality and achieve learning goals.